Therapeutic Effects of Punica granatum (Pomegranate): An Updated Review of Clinical Trials - Eghbali, Samira; Askari, Sayyedeh Fatemeh; Avan, Razieh; Sahebkar, Amirhossein (Journal of nutrition and metabolism, 2021)
Punica granatum L. belongs to the Punicaceae family which is distributed around the world. Different parts of pomegranate like seed, peel, juice, and leaves are rich in potential bioactive compounds. These plants have found application in traditional medicine such as in treatment of gastrointestinal, cardiovascular, and endocrine diseases, among others. The present review aimed to summarize the current research on the traditional and scientific applications of P. granatum with regard to the phytochemical content and clinical applications that may be useful for future drug development. Information about P. granatum was obtained from local classic herbal literature and electronic databases, such as PubMed, Scopus, and ScienceDirect. Several phytochemical constituents including polyphenolics, flavonoids, anthocyanosides, alkaloids, lignans, and triterpenes have been reported from the plant. Randomized clinical trials have provided evidence as to the pharmacological activities of pomegranate in several diseases including diabetes, cardiovascular disease, oral cavity disorders, endocrine disorders, and cancer. The present review has provided an insight into the traditional applications of the plants, and some of them have been validated by scientific evidence, particularly their applications as treatment of cardiovascular and endocrine diseases.